Nilai-Nilai Qir'ani sebagai Landasan Etika Pendidikan Inklusif - Nurul Fajriyah (GHAITSA : Islamic Education Journal, 2025)
This research aims to identify and analyze Qur'anic verses that can serve as ethical foundations (usūs akhlāqiyyah) for inclusive education. The methodology employed is qualitative literature study (dirāsah maktabiyyah naw'iyyah), analyzing relevant Qur'anic verses, namely Q. Al-Isra: 70, Al-Maidah: 8, and Al-Rum: 22, alongside classical and contemporary exegetical works (kutub al-tafsīr al-qadīmah wa al-mu'āṣirah) such as Tafsīr Al-Marāghī and Al-Misbāh. The research findings reveal three Qur'anic values (qiyam qur'āniyyah) that can serve as ethical foundations for inclusive education: the Value of Human Dignity (qīmat karāmat al-insān) (Q. Al-Isra), the Value of Justice (qīmat al-'adl) (Q. Al-Maidah), and Appreciation for Diversity (taqdir al-tanawwu') (Q. Al-Rum). These values form an ethical foundation (asās akhlāqī) for addressing discrimination and inequality in educational resources. Their integration enriches conventional inclusive models with spiritual perspectives (manāẓir rūḥiyyah) relevant to Muslim communities. This study concludes that Qur'anic values constitute a robust ethical foundation for inclusive education, offering holistic solutions (ḥulūl shāmilah) that combine educational equality with spirituality (rūḥāniyyah).